Linking Human Resource Development Practices and Organizational Commitment: Evidence from Nepalese Commercial Banks - Kharel, Shreekrishna; Niraula, Ganesh Prasad; Mainali, Bhawani Prasad (Journal of Nepalese Business Studies, 2024)
The primary goal of this research is to identify the key HRD practices that link organizational commitment and user predictability. The study employs causal-comparative research design and positivism epistemology. An analysis of associations' effects is done using a cross-sectional survey questionnaire. There were 46508 employees in the survey, and 384 of them were chosen as respondents based on a judgment from ten commercial banks in Nepal. A standardized Likert Scale questionnaire was used to collect data, with 1 denoting strongly disagree and 5 denoting strongly agree. The average Cronbach’s Alpha value for all the variables was 0.77, which has been used as a criterion to evaluate reliability. A total of 430 questionnaires were circulated, and 384 valid responses were collected. SPSS has been used to analyse the data. Regression analysis was used to estimate and forecast the associations. Results reveal that performance management was found to be inconsistent and insignificant, while all other variables that were found to be significant predictors of employee engagement (r2 = 0.648) included training and development, career advancement, and job security. This study also aims to demonstrate the need for proactive, all-encompassing approaches to factor efforts in order to emphasize organizational commitment and ensure alignment with business objectives in Nepalese commercial banks.